PENGARUH KARAKTERISTIK PEKERJAAN DAN KARAKTERISTIK INDIVIDU TERHADAP KEPUASAN KERJA PEGAWAI - RACHMAWATI, KARINA VITA (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2013)
ABSTRACT The objectives of this research are to investigate: (1) whether or not there is a significant effect of job characteristics on the job satisfaction of the employees in Muhammadiyah Hospital of Selogiri, Wonogiri in 2013; (2) whether or not there is a significant effect of individual characteristics on the job satisfaction of the employees in Muhammadiyah Hospital of Selogiri, Wonogiri in 2013; (3) whether or not there is a significant effect of job characteristics and individual characteristics on the job satisfaction of the employees in Muhammadiyah Hospital of Selogiri, Wonogiri in 2013. This research used the survey quantitative research method. Its population was all functional employees of Selogiri Muhammadiyah Hospital as many as 86 persons. The samples of the research consisted of 47 persons. They were taken by using the stratified proportional random sampling technique. The data of the research were gathered through questionnaire. They were then statistically analyzed by using the correlational and multiple regression analyses. The results of the research are as follows: (1) there is a significant effect of job characteristics on the job satisfaction of the employees in Muhammadiyah Hospital of Selogiri, Wonogiri as indicated by the value of rcount = 0.451 > rtable = 0.288; (2) there is a significant effect of individual characteristics on the job satisfaction of the employees in Muhammadiyah Hospital of Selogiri, Wonogiri as indicated by the value of rcount = 0.540 > rtable = 0.288; (3) there is a significant effect of job characteristics and individual characteristics on the job satisfaction of the employees in Muhammadiyah Hospital of Selogiri, Wonogiri as indicated by the value of Fcount = 14.602 > Ftable = 3.209. Other finding of the research is the multiple linear regression Y = -19.5 + 0.908X1 + 0.954 X2 meaning that the job satisfaction of the employees in Muhammadiyah Hospital of Selogiri Wonogiri index average will increase or decrease as much as 0.908 every time there is a one-unit increase or a one-unit decrease in the variable of job characteristics, and the job satisfaction index average will increase or decrease as much as 0.954 every time there is a one-unit increase or a one-unit decrease in the variable of individual characteristics. Each independent variable has a contribution to the dependent variable. The relative contribution of job characteristics to the employee?s job satisfaction is 38.2%, and that of individual characteristics to the employee?s job satisfaction is 61.68%. Furthermore, the effective contribution of job characteristics to the employee?s job satisfaction is 15.29% and that of individual characteristics to the employee?s job satisfaction is 24.62%. Keywords: job characteristics, individual characteristics, and job satisfaction, employee